Gemini/GMOS spectroscopy of the spheroid and globular cluster system of NGC 3923 - Norris, Mark A. (2008)
We present a technique to extract ultra-deep diffuse-light spectra from the standard multi-object spectroscopic observations used to investigate extragalactic globular cluster (GC) systems. This technique allows a clean extraction of the spectrum of the host galaxy diffuse light from the same slitlets as the GC targets. We show the utility of the method for investigating the kinematics and stellar populations of galaxies at radii much greater than usually probed in longslit studies, at no additional expense in terms of telescope time. To demonstrate this technique, we present Gemini South Multi-Object Spectrograph (GMOS) spectroscopy of 29 GCs associated with the elliptical galaxy NGC 3923. We compare the measured stellar population parameters of the GC system with those of the spheroid of NGC 3923 at the same projected radii, and find the GCs to have old ages >10 Gyr, [α/Fe] ∼ 0.3 and a range of metallicities running from [Z/H] = -1.8 to +0.35. The diffuse light of the galaxy is found to have ages, metallicities and [α/Fe] abundance ratios indistinguishable from those of the red GCs.